Pengaruh Kualitas Pelayanan dan Sarana Prasarana Terhadap Kepuasan Publik : Studi Tentang Pelayanan Pembuatan Akta Kelahiran di Dinas Kependudukan dan Catatan Sipil Kabupaten Ciamis - Ading Rahman Sukmara; Lelly Octaviany; Irma Bastaman (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This research is motivated by the results of initial observations that the quality of public services in birth certificate services at the Population and Civil Registration Office of Ciamis Regency still needs to be improved, considering the number of people who still do not have birth certificates is still large. Supporting infrastructure for services that are less noticed. This is evidenced by the lack of respect from the government in this case is the Population and Civil Registration Office of Ciamis Regency, in relation to the facilities and infrastructure of service providers. Not infrequently when people need birth certificates, there are no forms provided by the government to print birth certificates. The low public satisfaction with government services can also be seen from the quality of population services, there are still many complaints from the public regarding the quality of services of these agencies such as making certificates is still difficult and takes a long time compared to the normal time for completion, which can be more than a day. Therefore, many people will complain of irritation with the public services they receive. The influence of the quality of public services on Public Satisfaction. needs to be followed up. The method used in this study is a quantitative descriptive research method. The results of the study show that service quality has an effect on public satisfaction, with a level of influence in the sufficient category. This shows that service quality has a positive effect on public satisfaction. With quality service, it will open up opportunities to obtain maximum public satisfaction. Facilities and infrastructure have an effect on public satisfaction, with a level of influence in the sufficient category. This shows that facilities and infrastructure have a positive effect on public satisfaction. With the existence of facilities and infrastructure that support the implementation of services, it will open up opportunities to obtain maximum public satisfaction. The quality of service and facilities and infrastructure have an effect on public satisfaction, with a level of influence in the sufficient category. This shows that the quality of service and facilities and infrastructure have a positive effect on public satisfaction. With the existence of quality service and facilities and infrastructure that support the implementation of services, it will open up opportunities to obtain maximum public satisfaction